Audit Quality under Time Pressure and Fee Constraints: The Moderating Role of Auditor Motivation - Sari, Diah Ayu Wantika; Budiadnyani, Ni Putu; Sunarta, I Nyoman; Arlita, I G.A Desy (INVOICE : JURNAL ILMU AKUNTANSI, 2025)
This study investigates the influence of time budget pressure and audit fees on audit quality, incorporating auditor motivation as a moderating variable within Public Accounting Firms in Bali Province, Indonesia. Addressing a gap in the literature concerning the interplay between financial and temporal constraints and auditor performance, this research adopts a quantitative approach using Structural Equation Modeling (SEM) via SmartPLS. Data were obtained from 103 auditors through structured questionnaires. The empirical results demonstrate that time budget pressure has a significant positive effect on audit quality (β = 0.265, p = 0.006), as do audit fees (β = 0.246, p = 0.026). Notably, auditor motivation significantly moderates both relationships. Specifically, it amplifies the effect of time budget pressure (β = 0.369, p = 0.003) and audit fees (β = 0.198, p = 0.039) on audit quality. These findings suggest that auditor motivation plays a critical role in mitigating the negative implications of resource constraints and enhancing audit performance. The study contributes to the auditing literature by providing empirical evidence on the moderating role of intrinsic motivation in the audit process. From a practical perspective, it underscores the importance of professional development and equitable compensation strategies in supporting audit quality. Future research is encouraged to explore other contextual or behavioral moderators in different institutional or regulatory settings.